(untitled) (Konferensiyalar | Conferences, 2024)
This article provides a definition of critical thinking, the study of the goals and structure of technology, basic techniques, and a lesson model within the framework of this technology. Presentation of your experience, the use of this technology in literature and Russian language lessons, its effectiveness at different stages of lessons, in different types of lessons. Selection of didactic material for classes using this technology. Development of individual lesson elements, lesson models in accordance with the structure of this technology.